QUaD: A High-Resolution Cosmic Microwave Background Polarimeter - Hinderks, J.; Ade, P.A.R.; Bock, J.; Bowden, M.L.; Cahill, G.; Carlstrom, J.E.; Castro, P.G.; Church, S.; Culverhouse, T.; Friedman, R.; Ganga, K.; Gear, W.K.; et al. (American Astronomical Society, 2009)
We describe the QUaD experiment, a millimeter-wavelength polarimeter designed to observe the cosmic microwave background (CMB) from a site at the South Pole. The experiment comprises a 2.64 m Cassegrain telescope equipped with a cryogenically cooled receiver containing an array of 62 polarization-sensitive bolometers. The focal plane contains pixels at two different frequency bands, 100 GHz and 150 GHz, with angular resolutions of 5 and 3.5, respectively. The high angular resolution allows observation of CMB temperature and polarization anisotropies over a wide range of scales. The instrument commenced operation in early 2005 and collected science data during three successive Austral winter seasons of observation.